2010
DOI: 10.1007/s00268-010-0707-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet Counts after Transthoracic En Bloc Resection for Esophageal Cancer is Associated with Significantly Improved Survival

Abstract: Background We analyzed perioperative platelet counts as a potential clinical marker for survival after transthoracic en bloc resection for esophageal cancer. Recent data described preoperative thrombocytosis in malignancies to be associated with poor prognosis. Methods A retrospective analysis from a prospective database (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) was performed for 291 consecutive patients with esophageal cancer who underwent transthoracic en bloc esophagectomy and extended ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Consequences of thrombocytopenia, other than hemorrhage, are the delay and reduction of chemo- or radiotherapy to avoid a further decrease in platelet counts ( 41 ). Ling et al could show that an increase of platelets after the resection of esophagus carcinoma is associated with improved survival ( 42 ). In contrast, thrombocytosis in other malignant diseases correlated with poorer prognosis for recurrence-free and overall survival (OS) in several studies ( 5 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of thrombocytopenia, other than hemorrhage, are the delay and reduction of chemo- or radiotherapy to avoid a further decrease in platelet counts ( 41 ). Ling et al could show that an increase of platelets after the resection of esophagus carcinoma is associated with improved survival ( 42 ). In contrast, thrombocytosis in other malignant diseases correlated with poorer prognosis for recurrence-free and overall survival (OS) in several studies ( 5 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal cancer (SCC and AC), an increase in platelet count after en bloc resection has been reported to be associated with better prognosis in one study [19], and in a study from Pakistan, low preoperative platelet counts were associated with poor prognosis [20]. In contrast, another study found that preoperative thrombocytosis indicated poor prognosis in esophageal SCC [20].…”
Section: Discussionmentioning
confidence: 98%
“…This discordance may lead to between-study heterogeneity and affect the significance of results ( 16 ). For example, Shimada ( 27 ) and Ling ( 28 ) defined thrombocytosis as platelet count over 293×10 9 /L in esophagus tumor. They found thrombocytosis appeared in approximately 20% patients, whereas Aminian ( 29 ) and Dutta ( 30 ) reported a 3.4–4.46% incidence based on the 400×10 9 /L cutoff.…”
Section: Correlation Between Increased Platelet Counts and Cancer Prognosismentioning
confidence: 99%